(untitled) (Czech Journal of International Relations, 1967)
Anyone who attempts to clarify social processes and phenomena whose historical development has not yet been relatively completed and concluded exposes himself objectively to two dangers: either as a "chronicler" he objectively follows and describes the course of events in their chronological or logical sequence, and at the same time renounces the intention to evaluate , since he does not know which of the possibilities is hidden in each fact, they proceeded in this way, he risks that he will drown in a flood of facts, data and events, he will lose his orientation and will actually criticize the author for descriptiveness, making any effort to penetrate deeper to know the meaning and regularity of history difficult; or he will choose the second path, he will try to evaluate as much as possible, observe theoretically, draw lessons from historical laws and, on this basis, predict the likely direction of further development with conclusions for practical political activity, thereby exposing himself to the danger that history will not give him credit the truth, because "the course of the day cannot be talked about until after sunset".